Utilizing a Routing Table of Proactive MANET Routing Protocol to Monitor a Group of People Mobility - Trisnawan, Primantara Hari; Siregar, Reza Andria; Robbani, Dwindra Helmi (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
In general, a special group has a leader who is responsible for his or her members. The problem that often occurs in groups is the loss of members due to leaving the group. To overcome this problem, it is necessary to build a system that can help the leader monitor the members of his or her group by getting an alarm warning if there are members who have the potential to leave the group or even those who have left the group. Existing solution is using such one hop/direct communication, which may monitor each member too close. Then, our proposed system to overcome the limitation of a single hop wireless range is to monitor each member to some extent to reach multiple hops of wireless range. The system is developed using one of proactive MANET routing protocol, ie the Destination Sequenced Distance Vector (DSDV) protocol, and utilizes hop number information in the routing table to detect slave nodes (members' equipment) that have three or more hops from the master node (leader's equipment) or even if the slave node is lost. The testing on this system is carried out functionally and non-functionally. The results of functional testing show that the master node can produce an alarm warning in the form of a buzzer sound intermittently and the LED light flashes if there is a slave node with three number of hops or more and can produce an alarm warning in the form of a buzzer sound and the LED light flashes continuously if some slave nodes are lost. Routing table updates on this system have an average time of once every 92.445 seconds. The results of non-functional testing show that the average round trip time (RTT) required for the node to send broadcast messages is 0.208 seconds with 23 bytes of data and the average round trip time (RTT) to send SendMeYourNeighbour messages is 0.215 seconds with 43 bytes of data. Keywords: Routing table; Monitoring Mobility; Dynamic routing protocol; MANET; multihops; DSDV